The Role of Implications of Ind AS towards the Profitability of Pharmaceutical Companies through E-Pharmacy: A Study of Post Implications of Ind AS in India - Dr. Tina Shivnani, Mohammed Zeeshan Qadri (Journal of Informatics Education and Research, 2024)
In the view of the present scenario, the implications of Ind AS in India has opened numerous gates to reach to the market. The online pharma industries have emerged as new platform of e-commerce. Pharma industries has given so many facilities like, online consultation by reputed doctors across India and door to door delivery of medicines. Due to this facility, pharmaceutical industries have made huge profits. The paper reveals the recent upward shifts in the profitability of this industry due to the change in the standards. The data reflects that Pharma has earned double the profit in past few years. There are around 20 companies those are providing E- Pharmacy services in India, but a few companies are popular in market. In the same contest, it analyses the performance of these companies in Indian market. The data presented will show a significant change in the preferences of customers for buying medicines online along with . The customer has changed their perception towards the online trading of medicines due to huge margins, convenience for purchasing through online mode and receiving the medicines at doorstep.